اجهاد الشفقة لدي مستشاري التوجيه المدرسي والمهني - شنه,محمدرضا; حمامه,عمار (University of Eloued جامعة الوادي, 2024)
The current study addresses the issue of "compassion fatigue among counselors in educational and vocational guidance" in some high schools in El Oued province. The study aimed to investigate the level of compassion fatigue among the sample and to explore individual differences. To achieve these objectives, the study employed a descriptive methodology, utilizing exploratory and comparative approaches, deemed suitable for the nature of the subject. This was achieved through the implementation of a specially designed survey, developed after reviewing numerous studies and research that utilized similar measures for the same purpose. Following the validation of the psychometric properties of the instrument, it was applied to the main sample, consisting of 30 counselors, selected through a purposive, non-random method. The hypotheses were tested using the "t-test" for significance of differences. After data collection and analysis, the study arrived at the following conclusions: - A moderate level of compassion fatigue was found among the counselors in educational and vocational guidance. - No statistically significant individual differences in compassion fatigue were found among these counselors that could be attributed to the variable of gender. - No statistically significant individual differences in compassion fatigue were found among these counselors that could be attributed to the variable of age. ملخص: تعالج الدراسة الحالية موضوع "اجهاد الشفقة عند مستشاري الارشاد والتوجيه المدرسي والمهني" ببعض ثانويات ولاية الوادي، ولقد هدفت الدراسة إلى الكشف عن مستوى اجهاد الشفقة عند أفراد العينة والفروق الفردية. ولتحقيق الأهداف المذكورة اعتمدت الدراسة على المنهج الوصفي بأسلوبي الاستكشاف والمقارنة لملاءمته لطبيعة الموضوع، من خلال تطبيق أداة الاستبيان المعدة من طرفنا بعد الاطلاع على العديد من الدراسات والأبحاث التي استعملت مقاييس لنفس الغرض، وبعد التأكد من الخصائص السيكومترية للأداة تم تطبيقها على العينة الأساسية والتي بلغت (30) مستشار، واختيرت العينة بالطريقة غير العشوائية القصدية، حيث تمت معالجة الفرضيات باستخدام اختبار "ت" لدلالة الفروق، وبعد جمع البيانات ومعالجتها توصلت الدراسة إلى النتائج التالية: - مستوى متوسط من اجهاد الشفقة لدى مستشاري الارشاد والتوجيه المدرسي والمهني. - لا توجد فروق فردية ذات دلالة احصائية في اجهاد الشفقة لمستشار التوجيه والارشاد المدرسي والمهني التي تعزى إلى متغير الجنس - لا توجد فروق فردية ذات دلالة إحصائية في اجهاد الشفقة لمستشار التوجيه والإرشاد المدرسي والمهني التي تعزى إلى متغير السن.
Keywords: الاجهاد; الشفقة; Stress; Compassion; Compassion Fatigue; Guidance Counselor